Towards appreciating the importance of windowscapes: Evaluation and suggestion for improvement of New Zealand Building Code - Leila Mirza; Hugh Byrd (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
The rapid intensification of Auckland has made our visual awareness of the outdoor environment (windowscapes) more confined and restricted. The recent changes of Auckland’s windowscapes have made the shortcomings of the New Zealand Building Code more apparent. This paper aims to demonstrate the importance of windowscapes in urban dwellers’ life and suggest some changes to the current building code to provide healthier and liveable indoor environments. First, evidence from the literature on the impact of views on building occupants’ wellbeing will be reviewed. Then, New Zealand Code Clause (G7 Natural light) and its Acceptable Solution will be critically analysed to identify areas that require improvement.Our literature review indicates that private views are more relevant for health and wellbeing than building and planning legislation in New Zealand currently considers them to be. Hence, this paper suggests that windowscapes should become an essential part of future building codes and standards. This paper concludes that providing strict requirements regarding windowscapes is essential to building a healthier indoor environment.